Transboundary freshwater ecosystems in international law : the role and impact of the UNECE environmental regime - Moynihan, Ruby, 1984- (Cambridge : Cambridge University Press, 2021)
A global water crisis with far-reaching and interconnected environmental, social, health and economic impacts threatens the world. Healthy ecosystems and ecosystem services are degrading, and access to a sustainable water supply is increasingly inequitable both within and between States. This book demonstrates how to overcome the global freshwater ecosystem crisis by matching the scientific recommendations with an international legal framework fit for the task, which re-orientates international water law towards a stronger ecosystem approach that also protects vulnerable societies. It illustrates how to understand the fragmented legally binding and non-binding instruments of the United Nations Economic Commission for Europe environmental treaties as one coherent legal regime, which contributes to strengthening general rules and principles of the law concerning transboundary freshwater ecosystems. With the recent global opening of the UNECE regime, this book explores its potential role within the European region, Central Asia, Caucasus, Africa, the Middle East and beyond.
The role of international law in addressing the global freshwater ecosystem crisis -- Conceptualising the UNECE water and environmental regime - establishing the basis for coherent interpretation and institutional interaction -- Contemporary status of international law on transboundary freshwater ecosystems -- The common normative framework of the UNECE environmental regime and its contribution to international water law -- An ecosystem approach in international law concerning transboundary freshwater ecosystems -- Public participation - its contribution to procedural justice and intra-generational equity in a water scarce future -- River basin organisations, basin agreements and European environmental aw in the UNECE regime -- Transboundary freshwater ecosystems in international law : the role, impact and future of the UNECE environmental regime.
Title from publisher's bibliographic system (viewed on 04 Oct 2021).
Keywords: Water boundaries; Freshwater ecology; Water conservation -- Law and legislation; Fresh water -- Law and legislation; Environmental law, International